Comprehensive Physiology 2017
DOI: 10.1002/cphy.c160017
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Adipose Tissue Physiology

Abstract: The different types of adipose tissues fulfill a wide range of biological functions-from energy storage to hormone secretion and thermogenesis-many of which show pronounced variations over the course of the day. Such 24-h rhythms in physiology and behavior are coordinated by endogenous circadian clocks found in all tissues and cells, including adipocytes. At the molecular level, these clocks are based on interlocked transcriptional-translational feedback loops comprised of a set of clock genes/proteins. Tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 656 publications
0
42
0
12
Order By: Relevance
“…The circadian system and metabolic processes are intimately linked via complex behavioural, neural and endocrine pathways . Peripheral oscillators operative in liver, skeletal muscle, adipose tissue, thyroid gland, endocrine pancreas and other organs orchestrate physiological functions within these organs, adjusting them on a daily basis to the rest‐activity and feeding‐fasting cycles of the body . Genome‐wide transcriptome profiling studies of peripheral oscillators indicate that the temporal orchestration of metabolism and xenobiotic detoxification is a major purpose of circadian clocks in peripheral tissues .…”
Section: Body Metabolism Is Orchestrated By Circadian Clocks In Rodenmentioning
confidence: 99%
See 3 more Smart Citations
“…The circadian system and metabolic processes are intimately linked via complex behavioural, neural and endocrine pathways . Peripheral oscillators operative in liver, skeletal muscle, adipose tissue, thyroid gland, endocrine pancreas and other organs orchestrate physiological functions within these organs, adjusting them on a daily basis to the rest‐activity and feeding‐fasting cycles of the body . Genome‐wide transcriptome profiling studies of peripheral oscillators indicate that the temporal orchestration of metabolism and xenobiotic detoxification is a major purpose of circadian clocks in peripheral tissues .…”
Section: Body Metabolism Is Orchestrated By Circadian Clocks In Rodenmentioning
confidence: 99%
“…5,[26][27][28][29] Peripheral oscillators operative in liver, skeletal muscle, adipose tissue, thyroid gland, endocrine pancreas and other organs orchestrate physiological functions within these organs, adjusting them on a daily basis to the rest-activity and feeding-fasting cycles of the body. [30][31][32][33] Genome-wide transcriptome profiling studies of peripheral oscillators indicate that the temporal orchestration of metabolism and xenobiotic detoxification is a major purpose of circadian clocks in peripheral tissues. 27,30,[34][35][36][37][38][39][40][41][42][43][44][45][46][47] It was recently suggested that in mouse liver circadian gene expression is controlled by rhythmic chromatin interactions between enhancers and promoters.…”
Section: Body Metabolism Is Orchestrated By Circadian Clocks In Rodmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 There is a substantial amount of evidence demonstrating the importance of circadian rhythm in biological functions of metabolic tissues such as liver, muscle, and adipose tissue. [3][4][5] Accordingly, circadian disruption through shift work has been associated with numerous disorders related to a dysfunction in metabolic tissues, such as obesity, diabetes, and cardiovascular disease. [6][7][8] In addition, shift work has been associated with a low bone mineral density and increased fracture risk, 9,10 which are both hallmarks of the bone disease osteoporosis.…”
Section: Introductionmentioning
confidence: 99%